Foreign Exchange Rate Expectations: Micro Survey Data - Ito, Takatoshi (American Economic Review, 1990)
This paper analyzes the panel data of biweekly surveys on the yen/dollar exchange rate expectations of forty-four institutions for two years, and contains four major findings. First, market participants are heterogeneous; that is, significant "individual effects" exist in their expectation formation. Second, the individual effects have a characteristic of "wishful expectations": exporters expect yen depreciation, and importers expect yen appreciation (relative to others). Third, many violate the rational expectations hypothesis. Fourth, forecasts with long horizons showed less yen appreciation than those with short horizons. Cross-equation constraints implied by the consistency of the forecast term structure are strongly rejected in the data.